Pemeriksaan Antenatal Care (ANC) terhadap Penyakit Menular pada Ibu Hamil di Puskesmas Kampung Harapan, Kabupaten Jayapura - Herlando Sinaga (Jurusan Biologi FMIPA Universitas Cenderawasih, 2018)
Antenatal Care (ANC) is an effort to improve maternal and child health in Indonesia. ANC activities was done to avoid the level of vulnerability of pregnant women, although to date the maternal and infant mortality rates are still high. The low level of maternal knowledge and lack of husband's support to stimulate mothers to regularly do ANC causes low maternal participation in pregnancy visits. Some ANC examinations that are quite important because they are very influential on mother and child, for examples are the examination of syphilis, Human Immunodeficiency Virus (HIV), blood pressure and urine protein. This study aims to record the ANC examinations performed on pregnant women. This study was conducted at the Kampung Harapan Health Center Jayapura Regency from December 2017 to January 2018. The samples in this study are 30 people. Research method with Laboratory Exploratory Approach in the form of Treponerna Pallidum Haemagglutination Assay (TPHA) and Rapid Diagnostic Test (RDT), Blood Pressure Examination and 6% Acetic Acid Method. The results showed that 10% of sample is positive of syphilis and 10% of it was HIV positive. In addition, the results of the observations also showed that 47% of sample were known to have low blood pressure, while 53% of them had normal blood pressure. Examination of urine protein showed good results or 100% negative. Key words: antenatal care, syphilis, HIV, blood pressure, and urine protein.